2013
DOI: 10.1007/s00423-013-1143-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the outcomes of severe trauma patients from 15-year experience in a Western European trauma ICU of Emilia Romagna region (1996–2010). A population cross-sectional survey study

Abstract: Mortality of severe trauma decreased significantly during the last 15 years as well as mean GCS improved whereas mean ISS remained stable. The new safety regulations positively influenced incidence and severity of TBI and seemed to improve the outcomes. ISS seems to be a better predictor of outcome than RTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…Several studies have reported that such injuries mostly occur at the age of 30 to 40 years with 60 to 80% in the male gender. [2,3,8] In our study, median age was 36.9 and male gender was 78.9%. The main causes of blunt trauma injuries are road traffic accidents, followed by falls from height.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Several studies have reported that such injuries mostly occur at the age of 30 to 40 years with 60 to 80% in the male gender. [2,3,8] In our study, median age was 36.9 and male gender was 78.9%. The main causes of blunt trauma injuries are road traffic accidents, followed by falls from height.…”
Section: Discussionmentioning
confidence: 50%
“…The mortality rate has been reported to be lower in healthcare centers where trauma management is satisfactory. [3,6,7] FAST was first described by Rozycki and friends in 1996 and has an important role in the diagnoses of trauma patients in the ER. [9,10] FAST, which is rapid, easy to perform, cheap, and repeatable, can be performed in hemodynamically stable and unstable patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no agreement of opinions concerning trauma severity assessment criteria able to classify the injuries as polytrauma. When stratifying polytrauma patients, many authors rely on damage severity ranked on a scale of 16 and more with 17-25% risk of fatal outcome according to ISS (Injury Severity Score) [7,8]. Others [9] consider the presence of several injuries assigned 2 scores in no less than two anatomical regions according to AIS (Abbreviated Injury Scale) to be relevant for diagnosing polytrauma.…”
Section: Criteria For Polytrauma and Its Severitymentioning
confidence: 99%
“…Worldwide, multiple traumas are a leading cause of death (1). While in the nineties of the last century traumatic brain injury accounted for 58.4% of causes of death, the distribution of causes of death has changed today, showing a reduction of traumatic brain injuryrelated mortality but an increase of deaths due to multiple organ failure (MOF) and sepsis (2). Of interest, MOF after multiple traumas developed to the main mechanism leading to sepsis and death despite the major progress of intensive care management achieved during the last two decades (3).…”
mentioning
confidence: 99%